Implementation of Authentic Assessment in Islamic Cultural History Subject Within the Independent Curriculum - Sahlan, Moh; Abqoriy, Muhammad; Mawidha, Rahma Fajr (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2023)
This research aims to describe and analyze the implementation of authentic assessment in the "Kurikulum Merdeka" (independent curriculum) for the subject of Islamic cultural history at the Tsanawiyah madrasah level. The method used in this research uses qualitative research with a case study research design. This research was conducted at MAN 2 Banyuwangi with the observation, interview, and document study stages, supported by primary data using books, journal research, and relevant theories. The data collection techniques were interviews, documentation, observation, and questionnaires. The data analysis technique involved analyzing interactions through the steps of data collection, data reduction, and data presentation. This study's results indicate that the assessment implementation includes the cognitive, affective, and psychomotor domains. Assessment in the cognitive domain is in the form of written tests, oral tests, and assignments. Assessment in the affective domain is self-assessment and observation. Assessment in the psychomotor domain is in the form of assessment of performance, projects, products, and portfolios. Teachers faced obstacles in conducting authentic assessment activities, such as the complexity of instrument preparation, using numerous rubrics, too many points for each assessment, and limited time constraints.